Effect of mismatching abutments on implants with wider platforms - an experimental study in dogs - Baffone, Gabriele M. [UNESP]; Botticelli, Daniele [UNESP]; Canullo, Luigi; Scala, Alessandro [UNESP]; Beolchini, Marco; Lang, Niklaus P. (Wiley-Blackwell, 2012)
Aim: To evaluate the effect of mismatching abutments on implants with a wider platform on the peri-implant hard tissue remodeling and the soft tissue dimensions.Material and methods: Mandibular premolars and first molars of six Labrador dogs were extracted bilaterally. After 3 months of healing, one tapered implant was installed on each side of the mandibular molar region with the implant shoulder placed at the level of the buccal alveolar bony crest. on the right side of the mandible, an abutment of reduced diameter in relation to the platform of the implant was used, creating a mismatch of 0.85 mm (test), whereas an abutment of the same diameter of the implant platform was affixed in the left side of the mandible (control). The flaps were sutured to allow a non-submerged healing. After 4 months, the animals were sacrificed and ground sections were obtained for histometric assessment.Results: All implants were completely osseo-integrated. Bone levels were superior at the test than at the control sites. However, statistically significant differences were found only at the buccal and proximal aspects. The soft tissue vertical dimension was higher at the control compared with the test sites. However, statistically significant differences were demonstrated only at the buccal aspects.Conclusions: A mismatch of 0.85 mm between the implant and the abutment yielded more coronal levels of bone-to-implant contact and a reduced height of the peri-implant soft tissue (biologic width), especially at the buccal aspect, if the implant shoulder was placed flush with the level of the buccal alveolar bony crest.
Keywords: animal study; bone healing; bone levels; histometry; Implant dentistry; mismatching; oral implants; platform switching; soft tissue dimensions